Explicit solutions to a nonlocal 2-component complex modified Korteweg–de Vries equation. (February 2020) - Shi, Xujie; Lv, Pei; Qi, Cheng
Abstract: A nonlocal 2-component complex modified Korteweg–de Vries equation will be investigated in this paper. We derive the N -fold Darboux transformation in the form of determinants. Based on the plane wave solutions, explicit solutions can be generated via this N -fold Darboux transformation. Moreover, dynamical behaviours of nonsingular solutions are discussed.